Zaopatrzenie mieszkańców Łodzi w artykuły codziennego użytku w latach 1980–1983 - Lesiakowski, Krzysztof (Przegląd Nauk Historycznych, 2012)
Thousands of the so called „march of the hunger women” have proceeded at the end of July 1981 in Łódź. It was an expression of the deep displeasure from the citizen of the city for the tragically supply situation. Fact, that in Łódź, the most loudly protest cause, that it belongs to ask as supply of basic consumable article was formed in the period of legal activity of the movement „Solidarność” and how their availability has affected the martial law? The period 1980–1981 has brought many advantageous changes in sphere of civil liberty of the Polish people but it also meant catastrophe in the system of supply. At the end of the year 1981, in Łódź almost all was missing. It was possible to buy on introduce in this year of food coupon 70–80% due ration middling. The most critical situation was with provision of meat and meat product. Very fast after the installation of the martial law, it was seen that the military dictatorship will not mean a better life situation for the citizens of Łódź. On the contrary, a serious decrease of supply has follow, compare to the years 1980–1981. The symbol of this misery was the problem to get even bread in the first days after the 13th December 1981. Only the increase of prices and the keeping of the system of regulation protect the food market to completely fall down. It was no perspective of increasing the availability of the importing products at all, like ordinary tea. Supplies of articles of housekeeping were unforeseen entirely, furniture etc. In Łódź was missing also textile, clothes and shoes. Till the end of the martial law, it never happen in the supplying system some changements for better. It is possible to say in its final phase about stabilization of poverty only which meant farthest regress.